Evaluation of the cardiorrespiratory and hemogasometrics effects and cortisol plasmatic concentration in bovine submitted of electromagnetic immobilization Avaliação dos parâmetros cardiorrespiratórios, hemogasométricos e da concentração plasmática de cortisol em bovinos submetidos à imobilização eletromagnética - Moraes A.N.* (2009)
The ways of immobilization generally used in cattle provide excessive manipulation and stress for the animal. The pain is an emotional experience and unpleasant sensation in combination with tissue damage. The new method of physical restraint for cattle uses low intensity electromagnetic waves, promising immobilization without stress or painful stimulation for the animals. The aim of this study is to evaluate of cardiorespiratory effects and plasmatic cortisol concentration of cattle submitted to electromagnetic immobilization. Six healthy cows with average weight of 300.3 ± 85.76 kg (mean ± SD) were assigned to two treatments in a randomized design with a 15-day interval between experiments GC (control group) and GI (immobilization group). Data are presented as mean + SD. The statistical analyses used the t-Test between groups, and ANOVA random block design between times into same group. All statistical analyses were performed using P<0.05 as a significant level. Evaluation moments: M1 (basal); M1: after withdrawal probe, M2 and M3 (30 and 60 minutes after M1 respectively). There was a significant increase of FC and f in M1, PAM in the moments (M1, M2, M3) and in the levels of plasmatic cortisol concentration in M1 e M2 in the immobilization group when to compared with the control group. It could be concluded that this electromagnetic immobilization is a method of physic restraint only, offers no anesthetic support and favors comfort and animal welfare.